Impact modeling for the Double Asteroid Redirection Test (DART) mission. (August 2020) - Rainey, Emma S.G.; Stickle, Angela M.; Cheng, Andrew F.; Rivkin, Andrew S.; Chabot, Nancy L.; Barnouin, Olivier S.; Ernst, Carolyn M.; ,
Highlights: For homogeneous asteroid models, the DART impact outcome is primarily driven by a small number of material properties. Asteroid porosity and material strength at low pressure have the largest influence on the DART impact outcome. The momentum enhancement factor in the DART impact is predicted to be ~1.5–2. Abstract: We present results from numerical simulations of the DART impact using the CTH shock physics code with 2D homogenous asteroid models. A design of experiments approach was used to create a run matrix of 28 simulations varying 17 different material model inputs for the impactor and target. The resulting values of the momentum transfer efficiency factor β and the crater width and depth were analyzed to determine the relative sensitivity of each parameter for predicting the DART impact outcome. We found that β and crater width/depth ratio are primarily influenced by a small number of material model input parameters, a result which greatly reduces the parameter space required for more expensive 3D simulations.